SUSTAINABLE AGRICULTURAL PLANNING IN ORDER TO SUPPORT FOOD SECURITY (FOOD ESTATE) IN THE TIMANG GAJAH SUB-WATERSHED, BENER MERIAH REGENCY - Akbar, Halim; Praza, Riyandi; Authar ND, Muhammad (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
Good watershed management is the rational use of natural resources in the watershed to obtain maximum production in unlimited time, minimize the danger of damage (land degradation), and obtain an even water yield throughout the year. Timang Gajah sub-watershed with an area of 35,859.26 ha is one of the sub-watersheds of the Krueng Peusangan watershed. According to the results of research by Akbar et al. (2020), the Timang Gajah sub-watershed is included in the sub-watershed that needs to be restored. Judging from the critical land area, the Timang Gajah sub-watershed consists of very critical 2,398.47 ha, critical 23,989.87 ha, moderately critical 6,402.59 ha, potentially critical 3,063.97 ha and not essential 4.36 ha (BPDASHL, 2020). This shows that the Timang Gajah sub-watershed needs serious handling in its management. The purpose of this study is to develop a plan for sustainable use of agricultural land in the Timing Gajah sub-watershed that can reduce the rate of erosion (erosion < ETol) a decent income for each farmer (income > KHL). The cropping pattern planned in this study is a cropping pattern that supports food security (Food Estate). The research method that will be used in this research is a survey method which consists: 1) the preparation stage, 2) the preliminary survey stage, 3) the main survey stage and 4) the data analysis stage and the presentation of the results. The results showed that the predictive value of erosion obtained on mixed garden land use (SPL 2, 5, 12, 13 and 18) ranged from 18.70 - 103.81 tons/ha/year, while the ETol value ranged from 14.97 - 33.27 tons/ha/year. The predictive value of erosion on plantation land use (SPL 15) is 56.36 tons/ha/year, and the ETol value is 28.42 tons/ha/year. Meanwhile, the predicted erosion value for scrubland use (SPL 8, 9, 10, 11, 16 and 17) ranged from 23.81 - 73.67 tons/ha/year and ETol values 14.01 - 27.72 tons/year. Ha/year. The recommended intercropping pattern at the research location, especially in mixed garden land use, is potato and corn (A1) plus other businesses (livestock), potato and soybean (A2) intercropping, potato and peanut intercropping. Green (A3), intercropping of potato with chilli (A4) and monoculture potato plus other livestock business (A5) generate net income above decent living income for local farmers (Rp 66.400.000 / household/year).